2005
DOI: 10.1186/1471-2407-5-124
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of MUC genes in endometrial and cervical tissues and tumors

Abstract: Background: Mucin glycoprotein's are major components of mucus and are considered an important class of tumor associated antigens. The objective of this study was to investigate the expression of human MUC genes (MUC1, MUC2, MUC5B, MUC5AC and MUC8) in human endometrium and cervix, and to compare and quantitate the expression of MUC genes in normal and cancerous tissues.Methods: Slot blot techniques were used to study the MUC gene expression and quantitation.Results: Of the five-mucin genes studied, MUC1, MUC5B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 46 publications
6
15
0
Order By: Relevance
“…MUC1-Cter contains a CQCRRK motif that is necessary for nuclear localization of MUC1 and regulation of gene expression [11]. Despite extensive study of MUC1 in the context of breast and pancreatic cancers, there is limited understanding of MUC1 in endometrial cancer beyond expression studies [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…MUC1-Cter contains a CQCRRK motif that is necessary for nuclear localization of MUC1 and regulation of gene expression [11]. Despite extensive study of MUC1 in the context of breast and pancreatic cancers, there is limited understanding of MUC1 in endometrial cancer beyond expression studies [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…MUC8 mRNA levels are upregulated in middle ear effusions, chronic sinusitis, and endometrial adenocarcinomas Takeuchi et al, 2003;Hebbar et al, 2005]. In our previous study, we found that MUC8 mRNA levels were up-regulated in human nasal polyps epithelium whereas MUC5AC gene was not Yoon et al, 2002].…”
mentioning
confidence: 95%
“…T he epithelial mucin MUC1 is a large transmembrane glycoprotein that is expressed on the apical surface of healthy ductal epithelia and also on a broad range of adenocarcinomas (1)(2)(3)(4)(5). The ability of Abs and T cells to distinguish between normal and tumor-specific glycoforms of MUC1 makes this molecule an attractive immunological target for the treatment of many cancers of epithelial origin (6).…”
mentioning
confidence: 99%